Pengaruh Model Pembelajaran Terhadap Perkembangan Pendidikan di Sekolah - Oktariani; Linda Hernawati; Siti Rukiah; Dessy Wardiah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The learning method requires a resistance method, namely the ability of the teacher to listen to students who are able to speak, read, practice and carry out learning actions tentatively and constructively, in order to be able to create a more lively, easy and careful atmosphere of learning. This research is a qualitative research using an opinion survey approach observing SMAN 1 Muara Sugihan, Banyuasin. This study aims to determine the effect of the learning model on the learning outcomes of class XII students in the 2021/2022 academic year. The population of this research is all students of class XII in the academic year 2021/2022. The sample used in this study was purposive sampling, in this case the researcher chose class XII, which consisted of 30 people, to be used as samples in this study. In this study, the researchers used a quantitative method to test the hypothesis by using a hypothesis technique, the hypothesis technique used was the t-test hypothesis. The results of this study indicate that the learning model has an average value of 20.15-23.25 with a high category and learning outcomes have 18.90 with a sufficient category. This is supported by the results of the t-test hypothesis testing where the value is 78.34% with a significance of 0.01. . So Ha is accepted, that is, there is a significant influence between the learning model and the learning outcomes. From the results of this study it can be concluded that the learning model has an influence on student learning outcomes.